SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL STUDIES OF SOME DIVALENT METAL(II) COMPLEXES DERIVED FROM 1-[(4-IODO-PHENYLIMINO)-METHYL]-NAPHTHALEN-2-OL SCHIFF BASE (FUDMA JOURNAL OF SCIENCES, 2021)
Schiff base derived from condensation of 2-hydroxy-1-naphthaldehyde and 4-iodoaniline was synthesized and used for the preparation of Co(II) and Ni(II) complexes. The complexes were characterized by IR, Powder-XRD, Solubility test, thermal analysis, conductivity measurement, magnetic susceptibility and elemental micro analysis. IR study indicated a strong band in the spectra of the Schiff base at 1603 cm-1 assigned to azomethine v(C=N) stretching vibration. It shifted to new frequency regions (1618 - 1622 cm-1) in the spectra of the complexes indicating the formation of the desired complexes. The decomposition temperatures of the complexes are in the range of (260-265) oC , molar conductance values are in the range of (4.51 -11.31) Ohm-1cm2 mol-1, indicating non electrolytic nature of the synthesized complexes in DMF. Magnetic susceptibility measurement indicated that Co(II) and Ni(II)  complexes are  paramagnetic and exhibit magnetic moment in the range of 2.92-3.24 BM, the values correspond to the square planar geometry. The Powder x-ray diffraction analysis showed the patterns of the metal(II) complexes were different from the reactants, signifying that reactants were changed to product. The CHN analysis results show the formation of 1:2 metal to ligand ratio. The synthesized compounds have been studied for antimicrobial activity using pathogenic bacteria and fungal pathogens by disc diffusion method. The results indicated that metal complexes (10 â€“ 15 mm inhibition zone) are more active compared to Schiff base (8 â€“ 12 mm inhibition zone) against the test organisms.
Keywords: Schiff base, Complexes, azomethine, 4-Iodoaniline, 2-hydroxy-1-naphthaldehyde